Wolbachia infections in world populations of bean beetles (Coleoptera: Chrysomelidae: Bruchinae) infesting cultivated and wild legumes - Kondo N.I. (2014)
Wolbachia endosymbionts are widespread among insects and other arthropods, often causing cytoplasmic incompatibility and other reproductive phenotypes in their hosts. Recently, possibilities of Wolbachia-mediated pest control and management have been proposed, and the bean beetles of the subfamily Bruchinae are known as serious pests of harvested and stored beans worldwide. Here we investigated Wolbachia infections in bean beetles from the world, representing seven genera, 20 species and 87 populations. Of 20 species examined, Wolbachia infections were detected in four species, Megabruchidius sophorae, Callosobruchus analis, C. latealbus and C. chinensis. Infection frequencies were partial in M. sophorae but perfect in the other species. In addition to C. chinensis described in the previous studies, C. latealbus was infected with two distinct Wolbachia strains. These Wolbachia strains from the bean beetles were phylogenetically not closely related to each other. Among world populations of C. chinensis, some Taiwanese populations on a wild leguminous plant, Rhynchosia minima, exhibited a peculiar Wolbachia infection pattern, suggesting the possibility that these populations comprise a distinct host race or a cryptic species. © 2011 Zoological Society of Japan.